Burden of hospitalized childhood community-acquired pneumonia: A retrospective cross-sectional study in Vietnam, Malaysia, Indonesia and the Republic of Korea - Kah Kee Tan; Duc Anh Dang; Ki Hwan Kim; Cissy Kartasasmita; Hwang Min Kim; Xu-Hao Zhang; Fakrudeen Shafi; Ta-Wen Yu; Emilio Ledesma; Nadia Meyer (Taylor & Francis Group, 2018)
Background: Few studies describe the community-acquired pneumonia (CAP) burden in children in Asia. We estimated the proportion of all CAP hospitalizations in children from nine hospitals across the Republic of Korea (high-income), Indonesia, Malaysia (middle-income), and Vietnam (low/middle-income). Methods: Over a one or two-year period, children <5 years hospitalized with CAP were identified using ICD-10 discharge codes. Cases were matched to standardized definitions of suspected (S-CAP), confirmed (C-CAP), or bacterial CAP (B-CAP) used in a pneumococcal conjugate vaccine efficacy study (COMPAS). Median total direct medical costs of CAP-related hospitalizations were calculated. Results: Vietnam (three centers): 7591 CAP episodes were identified with 4.3% (95% confidence interval 4.2;4.4) S-CAP, 3.3% (3.2;3.4) C-CAP and 1.4% (1.3;1.4) B-CAP episodes of all-cause hospitalization in children aged <5 years. The B-CAP case fatality rate (CFR) was 1.3%. Malaysia (two centers): 1027 CAP episodes were identified with 2.7% (2.6;2.9); 2.6% (2.4;2.8); 0.04% (0.04;0.1) due to S-CAP, C-CAP, and B-CAP, respectively. One child with B-CAP died. Indonesia (one center): 960 CAP episodes identified with 18.0% (17.0;19.1); 16.8% (15.8;17.9); 0.3% (0.2;0.4) due to S-CAP, C-CAP, and B-CAP, respectively. The B-CAP CFR was 20%. Korea (three centers): 3151 CAP episodes were identified with 21.1% (20.4;21.7); 11.8% (11.2;12.3); 2.4% (2.1;2.7) due to S-CAP, C-CAP, and B-CAP, respectively. There were no deaths. Costs: CAP-related hospitalization costs were highest for B-CAP episodes: 145.00 (Vietnam) to 1013.3 USD (Korea) per episode. Conclusion: CAP hospitalization causes an important health and cost burden in all four countries studied (NMRR-12-50-10793).